2015
DOI: 10.1016/j.copsyc.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy to prevent depressive relapse in adults

Abstract: The high prevalence, frequent relapse, and recurrence of major depressive disorder (MDD) increase its personal and societal costs. Cognitive therapy (CT) aims to decrease depressive symptoms and prevent relapse/recurrence. We review prevention evidence for acute, continuation, and maintenance CTs for patients whose depression is active, remitted, and recovered, respectively. Evidence suggests that patients relapse less often after discontinuing acute phase CT versus discontinuing pharmacotherapy. Continuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Relapse rates ranged from 29% over 14 months to 60% over 6 years and up to 87% over 10 years follow-up. 18 Next to improved relapse rates, we found that CBTbased strategies (combined with ADMc) are associated with increased time to relapse, which is closely comparable to findings in previous meta-analyses in adults (eg, see 6,[17][18][19][20][21] ). There was a small difference between CBT-based strategies and CAU control conditions on mean depressive symptoms at last follow-up, which was not found in the previous meta-analysis in youth.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Relapse rates ranged from 29% over 14 months to 60% over 6 years and up to 87% over 10 years follow-up. 18 Next to improved relapse rates, we found that CBTbased strategies (combined with ADMc) are associated with increased time to relapse, which is closely comparable to findings in previous meta-analyses in adults (eg, see 6,[17][18][19][20][21] ). There was a small difference between CBT-based strategies and CAU control conditions on mean depressive symptoms at last follow-up, which was not found in the previous meta-analysis in youth.…”
Section: Discussionsupporting
confidence: 86%
“…Two main relapse prevention strategies are often used: antidepressant medication (ADM) continuation (ADMc) (eg, see 11,14 ) and psychological interventions (or the combination) (eg, see [15][16][17][18] ). ADMc and psychological strategies started after remission are associated with reduced risk of relapse and prolonged time to relapse in adults remitted from MDD (eg, see 6,17,[19][20][21] ). There is even metaanalytic evidence that psychological relapse prevention strategies (ie, mindfulness-based cognitive therapy and preventive cognitive therapy) are an alternative for ADMc in recurrent MDD (eg, see 18,21 ).…”
mentioning
confidence: 99%
“…Research shows that a majority of patients (40%–60%; Vittengl et al, 2016; Waltman, Creed, & Beck, 2016) benefit from CBT, but only one third experience a full remission from depression (Hollon et al, 2002; Waltman et al, 2016). And, of those who experience a full remission, more than one quarter of them will relapse within 2 years (Hollon et al, 2002; Jarrett, Minhajuddin, Gershenfeld, Friedman, & Thase, 2013; Vittengl, Clark, Dunn, & Jarrett, 2007; Vittengl & Jarrett, 2015). Furthermore, a modeling exercise by Andrews, Issakidis, Sanderson, Corry, and Lapsley (2004) found that if every individual with depression received an empirically supported treatment such as CBT, it would avert only 34% of the global burden of the depression (i.e., years lived with disability).…”
mentioning
confidence: 99%
“…In addition to the treatment of acute episodes of depression, CBT has been used to prevent the recurrence of depression among people who have recently remitted from a depressive episode. Vittengl and Jarrett (2015) review this literature, including a very large recent study they completed that examining the effectiveness of continuing CT for reducing depressive relapse. Importantly, they also highlight who is most likely to benefit from this form of treatment and identify important future directions for work in this important area.…”
Section: Established Treatmentsmentioning
confidence: 99%